Evaluating the Efficiency and Staff Satisfaction of the Point-of-Care IV Activated System Versus Traditional Piggyback in Administering IV Antibiotics at a Saudi Tertiary Hospital - Khaled Elshammaa; Abubakr A. Yousif; Abdullah Alshammari; Mohammed Alnuhait; Abdulmalik S. Alotaibi; Mahmoud E. Elrggal; Mohamed Hassan Elnaem (MDPI AG, 2024)
Background: This study aims to compare resource utilization and staff satisfaction between the point-of-care (POC) activated system and the traditional intravenous piggyback (PB) system in hospital pharmacy settings. Methods: Employing a pre-post quasi-experimental design from November 2019 to April 2020, the study assessed resource requirements for both the POC activated system and the traditional PB system. Additionally, a staff satisfaction survey was conducted, focusing on staff experiences related to the pharmacy preparation process and the subsequent activation of the system by nurses. Results: The POC activated system required significantly fewer full-time equivalents (FTEs) per month compared to the PB system (0.36 ± 0.05 vs. 1.56 ± 0.07; p < 0.0001). Using POC in automated dispensing cabinets (ADCs) reduced medication administration time and returns (6.41% vs. 1.75%; p < 0.0001). The staff satisfaction survey revealed greater satisfaction with the POC activated system. A subsequent analysis showed the POC activated system had a low expiration rate of 0.1% and a cost of 39 Saudi riyal, while the traditional system had higher expiration rates and cost of 46,260 SR. Conclusions: The POC activated system reduced FTEs, decreased returned medications, and enhanced staff satisfaction compared to the PB system.